Elt materials: the key to fostering effective teaching and learning settings (2009)
Our article aims at providing teachers with an overview for materials development, taking into account the experience gained by two teachers in the English Programme of the School of Education at Universidad Externado de Colombia in Bogotá. This experience has helped us achieve better teaching and learning conditions for our university students in their quest to learn a foreign language. This paper addresses the issue of the role of teachers as textbook developers, and how they can meet materials development demands by integrating a clear conceptualisation and set of principles as well as their essential components. Key words: Materials development, text developers, materials development demands, effective teaching and learning settings Este artículo brinda a los profesores de inglés un panorama del desarrollo de materiales con base en nuestra experiencia como profesoras del Programa de Inglés de la Facultad de Educación de la Universidad Externado de Colombia, en Bogotá. Esta experiencia ha permitido mejorar las condiciones de aprendizaje de nuestros estudiantes de inglés como lengua extrajera. El documento se centra en el papel de los profesores como diseñadores de textos para cursos de inglés, y cómo ellos pueden satisfacer las exigencias que demanda el desarrollo de materiales, integrando una clara conceptualización, sus principios y sus componentes esenciales. Palabras clave: Diseño de materiales, diseñadores de textos, requisitos para el desarrollo de materiales, ambientes efectivos de enseñanza-aprendizaje